A Green Human Resources Management: A Systematic Literature Review (SLR) - Frederik Pradana Deniswara; Sopiah Sopiah (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Green human resource practices in this era have been applied in all areas of company activity. The purpose of this systematic literature review is to analyse how Green Human Resources Management is implemented using the Preferred Reporting Items for Systematic Review method. Data were obtained from online databases, namely Taylor and Francis, Emerald Insight, SAGE, Springer, Frontiers, MDPI, and Dovepress (2019 - 2023) and 40 articles were obtained. By using the keyword search "green human resource management". The results of the analysis obtained that the implementation of green human resource practices and has an implementation of environmental performance, green employee behaviour, sustainability practices, green innovation, green behaviour, green recruitment and selection, green development and training.